2001
DOI: 10.1038/35096564
|View full text |Cite
|
Sign up to set email alerts
|

Histamine regulates T-cell and antibody responses by differential expression of H1 and H2 receptors

Abstract: Many pathological processes, including those causing allergies and autoimmune diseases, are associated with the presence of specialized subsets of T helper cells (TH1 and TH2) at the site of inflammation. The diversity of TH1 and TH2 function is not predetermined but depends on signals that drive the cells towards either subset. Histamine, released from effector cells (mast cells and basophils) during inflammatory reactions can influence immune response. Here we report that histamine enhances TH1-type response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
455
2
16

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(491 citation statements)
references
References 28 publications
18
455
2
16
Order By: Relevance
“…Neither H2R antagonist (ranitidine) nor H3R antagonist/H4R-partial agonist (clobenpropit) had any impact on histamine binding to the Th1 cells. This study demonstrated the expression of H1Rs on Th1 cells and H2Rs on Th2 cells by antibodies generated against the H1R and H2R [6].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Neither H2R antagonist (ranitidine) nor H3R antagonist/H4R-partial agonist (clobenpropit) had any impact on histamine binding to the Th1 cells. This study demonstrated the expression of H1Rs on Th1 cells and H2Rs on Th2 cells by antibodies generated against the H1R and H2R [6].…”
Section: Introductionmentioning
confidence: 67%
“…Histamine is a potent agonist of all four receptors (H1-H4) [6,13,14] that are distributed in different parts of body. These receptors modulate different biochemical, pharmacological and immunological reactions, both in vivo and in vitro, by activating signal transduction pathways for endogenous histamine release [13].…”
Section: Immunomodulatory Profile By H1 and H2 Agonists And Antagonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Histamine negatively regulates T helper (T H 1 and T H 2) cell responses through the H 2 receptor and H 2 receptor knockout mice show upregulation of T H 1 and T H 2 cytokines (Jutel et al, 2001). Increased release of histamine has been proposed as the cause of the immunosuppression seen at the time of colonic resection and several studies have shown that perioperative H 2 receptor antagonists can prevent this effect, thereby improving immune surveillance at the time of surgery (Adams et al, 1994b).…”
mentioning
confidence: 99%